No man is an island: The sustainability awareness effect of geography on hedonic fashion consumption and connection with nature ‐ evidence from Galápagos and Hawaii. Issue 1 (1st October 2021) - Pohlmann, Attila
The demand for ever-accelerating fast fashion is unprecedented, while its supply chain burdens environmental systems. Hedonic fashion consumption is generally unfettered by sustainability concerns, but evidence suggests that island geographies‐with dense boundaries between the built and the natural environment‐have a heightening effect on eco-consciousness. A framework based on the contemporary condition of hyperconsumption is proposed: island geography heightens sustainability awareness; consequently, fashion consumers located on islands trade-off perceived hedonic benefits of fashion consumption against perceived moral benefits of connection with nature. The framework is supported by visual evidence collected on the Galápagos island Santa Cruz, indicating that male fashion consumers express connection with nature by means of tattoos, slogans on clothing and choice of eco-friendly materials. Quantitative tests with survey data from the United States and Ecuador show that residents in Hawaii and the Galápagos have higher levels of connection with nature compared to residents on the associated continental areas. This effect is mediated by decreased perceived rewards of hedonic fashion consumption, but the effect is overall weaker in Ecuador compared to the United States due to differences in purchasing power and attitudes towards consumerism. Because of the stereotype that eco-friendly is unmanly, men are generally less likely to embrace environmentally friendly products and the findings of this research point to avenues to overcome this barrier.